Oil Content, Fatty Acid and Phenolic Profiles of Some Olive Varieties Growing in Lebanon - El Riachy, Milad; Hamade, Athar; Ayoub, Rabih; Dandachi, Faten; Chalak, Lamis (Frontiers in Nutrition, 2019)
Olive growing in Lebanon has an important role at both social and economic level. Nevertheless, olive oil quality produced in Lebanon has been rarely addressed. In this study, oil content, fatty acid and phenolic profiles were studied along four different ripening stages for 11 varieties of which two clones of the local variety ‘Baladi’, in addition to nine foreign varieties (‘Ascolana Tenera’, ‘Bella di Cerignola’, ‘Itrana’, ‘Jabaa’, ‘Kalamata’, ‘Nabali’, ‘Salonenque’, ‘Sigoise’ and ‘Tanche’). Oil content was determined by Soxhlet method and Abencor system. Fatty acid composition was determined using a GC-FID, total phenols by spectrophotometry, and the phenolic profile using HPLC-DAD. Results showed that variety, fruit ripening and their interaction have significant effect on the overall studied oil parameters. Among the studied varieties, ‘Kalamata’ presented the higher oil content on dry matter (OCDM = 48.24%), ‘Baladi 1’ the highest oil content on humid matter (OCHM = 27.86%), and ‘Tanche’ the highest oil industrial yield (OIY = 19.44%). While ‘Tanche’ recorded the highest C18:1 (71.75%), ‘Ascolana Tenera’ showed the highest total phenols (TP=539.27 mg GAE/Kg of oil), ‘Salonenque’ the highest oleacein (121.57 mg/Kg), and ‘Itrana’ the highest oleocanthal contents (317.68 mg/Kg). On the other hand, oil content together with C18:2 and C18:0 increased along ripening while C18:1, total phenols and the main individual phenols decreased. Although preliminary, this study highlights the good quality of the olive oil produced from both local and foreign varieties growing in Lebanon, and incites to conduct further investigations for the characterization and authentication of the Lebanese olive oil.